Determinants of the Regional Demand for Higher Education - Carla Sá; Raymond J.G.M. Florax; Piet Rietveld (Tinbergen Institute, 2003)
Studies on the determinants of the demand for higher education typically emphasizethe relevance of socio-economic factors, but leave the spatial dimensions of the prospectivestudents' university choices largely unexplored. In this study, we investigate the determinantsof university entrance for Dutch high school graduates in 2000, and pay particular attention tothe attractiveness of the university, both in terms of its accessibility and the educationalquality of its programme. We combine cross-section data on the region of origin of the highschool graduate and the university destination region for first-year students with regional anduniversity characteristics in a production-constrained gravity model. The main finding of thestudy is that the behaviour of prospective students is governed by a negative distancedeterrence effect and a downward rent effect, but a positive impact results from regional/urbanamenities rather than from the educational quality of the university programmes.
Keywords: I21; J24; O15; R23; 330; Demand for higher education; gravity model; education quality; agglomeration economies.; Bildung; Studium; Bildungsverhalten; Niederlande